Global hotspot and trend of extracorporeal membrane oxygenation for pulmonary embolism - Wang, Wei; Ji, Jianyu; Han, Lin; Pang, Jing; Mo, Li; Liu, Fang; Gao, Yamin; Xiong, Bin; Xiang, Shulin (Frontiers in Medicine, 2025)
BackgroundResearch on extracorporeal membrane oxygenation (ECMO)-assisted support for pulmonary embolism (PE) has been increasing, yet no systematic bibliometric analysis has been conducted. This study evaluates global research trends in this field by analyzing countries, institutions, authors, journals, references, and keywords.MethodsRelevant articles and reviews published up to August 15, 2023, were retrieved from the Web of Science Core Collection (WOSCC). VOSviewer and CiteSpace software were used for bibliometric analysis of collected data.ResultsPublications on ECMO-assisted support for PE surged from 2015 to 2023, comprising 82.7% (306/370) of total studies. The United States, Germany, and China contributed 62.97% (233/370) of the research. Perfusion-UK had the most publications, while Journal of the American College of Cardiology was the most cited journal. The University of Maryland, Massachusetts General Hospital, and Harvard Medical School were the leading institutions. Chetan Pasrija published the highest number of papers, while Konstantinidis SV was the most co-cited author. Research hot spots include: (1) ECMO management and survival rates, (2) combined treatments with thrombolysis or surgical thrombectomy, (3) anticoagulation and clot formation, and (4) ECMO support in COVID-19.ConclusionThis study aims to increase awareness of research hot spots on ECMO-assisted support for PE by determining the collaboration and impact of authors, countries, institutions, and journals. In addition, it comprehensively reviews research trends on ECMO regarding PE. It also provides a reference for potential collaborators, institutions, and future research prospects.